Evaluation for antiviral potential of ficus deltoidea against dengue virus type-2 - Yuan, Seng Wu; Afzal, Sheryar; V. Appalaraju; Tan, Qi Wei; Aimi Syamima Abdul Manap; Albokhadaim, Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Dengue is one of the most widespread arthropod-borne viral diseases that cause negative impact globally. Presently, no effective drug is available to safeguard people against dengue. Ficus deltoidea is Malaysia›s famous traditional herb belonging to Moraceae family due to its pharmacological potential. F. deltoidea leaves (FDL) were extracted with n-hexane, ethyl acetate and methanol. Cell cytotoxicity study using MTT assay measuring the formazan absorbance was conducted to determine maximum non-toxic concentration on Vero cells. The antiviral activities of various concentrations of FDL extracts were assessed using virus reduction neutralisation tests against dengue virus type 2. The CC20 value of n-hexane, ethyl acetate and methanol FDL extracts were 2.99 ± 0.31, 22.15 ± 2.39, and 25.22 ± 0.42 µg/mL, respectively. Methanol FDL extract at maximum non-toxic concentration exerted strongest direct extracellular virucidal effect against DENV-2. In cell protection assay, ethyl acetate FDL extract achieved highest reduction in viral infectivity (98.17%), whereas n-hexane FDL extract showed strongest inhibition in DENV-2 viral replication in post-infection assay. Methanol FDL extract showed highest selectivity index value in direct virus inhibition, cell protection and post-infection assay. Conclusively, FDL extracts, especially methanol FDL showed potential antiviral activity against DENV-2, thus considered as promising anti-dengue agent.